Auricular acupoint pressing therapy and nursing management for insomnia in a patient with central retinal artery occlusion (耳穴压丸治疗1例视网膜中央动脉阻塞患者失眠的护理体会) - GENG Lina (耿丽娜); YANG Jianying (杨剑英); WANG Luxia (王璐霞); LI Na (李娜) (中西医结合护理)
This paper summarized the auricular acupoint pressing therapy an nursing measures for insomnia in a patient with central retinal artery occlusion. On the basis of nursing risk assessment, Traditional Chinese Medicine auricular acupoint pressing therapy was adopted. Comprehensive nursing interventions such as strengthening cooperation between medical and nursing care, providing oxygen therapy according to the doctor's advice, enhancing the psychological care and diet care of patients were carried out during the treatment. Traditional Chinese Medicine auricular acupoint pressing therapy can effectively relieve the psychological stress and improve the sleep quality of the patient. (本文总结1例采用耳穴压丸治疗视网膜中央动脉阻塞(CRAO)后失眠的护理经验。在完善护理评估的基础上, 采用中医耳穴压丸治疗, 同时积极配合医生进行救治, 遵医嘱及时给予安全的氧疗护理, 加强患者的心理护理和饮食护理, 有助于缓解患者心理压力, 改善睡眠质量。)